Proposing clinician competency guidelines for the inclusion of disability in the undergraduate medical curriculum of South Africa - an exploratory study - Whitehead, Sarah Nicole (Department of Health Sciences Education, 2023)
Introduction Persons with disability make up the largest minority group in the world yet there is a dearth of research both internationally and nationally on how disability is included in professional training curricula for medical doctors. Aim of the study The purpose of this study is to add to the body of knowledge that would facilitate the inclusion of disability in the undergraduate medical curriculum in South Africa. Methods This is a mixed method, sequential study – Phase one followed by Phase two. Phase one, data was collected - via focus groups and in-depth interviews - from Medical Doctors, Medical Students, Physiotherapists, Occupational Therapists, Speech and Language Therapists and Persons with disability. Phase two used a modified Delphi Method with an expert panel of disabled and abled Disability Studies Academics, Medical Educators, Disability Rights Activists and Medical Doctors. The experts were asked to rate – using a 5-point Likert Scale - each competency according to its importance and language clarity. They were also asked in open-ended questions, to make any suggestions relating to the language of each competency and whether any competencies could be combined. 2 Findings Four main themes emerged from Phase one data: Experience of disability, Attitudes towards disability, Knowledge about Disability and Life beyond the disability. Data from these four themes contributed to the generation of an initial competency set – 17 competencies and 13 sub-competencies. In Phase two the initial competency set was presented to an expert panel as part of a modified Delphi Method. In the first iteration consensus was regarding the importance of each competency. In the second iteration consensus was reached regarding the language of each competency and a final competency set – containing 13 competencies and 9 sub-competencies - was generated. Competencies and sub-competencies 1-6 are clustered as knowledge competencies, 7-10 as attitudes and 11-13 as skills. Conclusion This study sets an important precedent for the inclusion of the subject of disability in undergraduate medical curricula. It proposes an approach to teaching and learning about disability inclusion for medical students. The list of disability specific competencies set forth by this study are a steppingstone in the process of curriculum transformation. The use of this guideline to improve the understanding of disability, and as a catalyst for undergraduate medical curriculum review is recommended.